Bottom currents in the jurassic-cretaceous vaca muerta formation black shales (argentina): an example of benthos response to oxygen delivery in oxygendeficient environments - Paz, Maximiliano (2018)
Fil: Paz, Maximiliano. University of Saskatchewan, Department of Geological Sciences, 114 Science Place, S7N 5E2 Saskatoon, Canada